Control of aggregated structure of photovoltaic polymers for high‐efficiency solar cells. Issue 5 (5th May 2021) - Gao, Mengyuan; Wang, Wenxuan; Hou, Jianhui; Ye, Long
Abstract: π‐Conjugated organic/polymer materials‐based solar cells have attracted tremendous research interest in the fields of chemistry, physics, materials science, and energy science. To date, the best‐performance polymer solar cells (PSCs) have achieved power conversion efficiencies exceeding 18%, mostly driven by the molecular design and device structure optimization of the photovoltaic materials. This review article provides a comprehensive overview of the key advances and current status in aggregated structure research of PSCs. Here, we start by providing a brief tutorial on the aggregated structure of photovoltaic polymers. The characteristic parameters at different length scales and the associated characterization techniques are overviewed. Subsequently, a variety of effective strategies to control the aggregated structure of photovoltaic polymers are discussed for polymer:fullerene solar cells and polymer:nonfullerene small molecule solar cells. Particularly, the control strategies for achieving record efficiencies in each type of PSCs are highlighted. More importantly, the in‐depth structure–performance relationships are demonstrated with selected examples. Finally, future challenges and research prospects on understanding and optimizing the aggregated structure of photovoltaic polymers and their blends are provided. Abstract : A comprehensive overview of the key advances and current status in aggregated structure research of photovoltaic polymers was presented. This review provided a tutorial on the multi‐level aggregated structure and the characteristic parameters as well as the associated characterization techniques. To in‐depth understand the structure‐performance relationships, effective strategies to control the aggregated structure of photovoltaic polymers are summarized, with an emphasis on the systems of record‐high power conversion efficiencies.